Daily Effects of Foreign Exchange Intervention: Evidence from Official Bank of Canada Data - Rasmus Fatum (University of Copenhagen, Economic Policy Research Unit (EPRU), 2005)
This paper analyzes the effects of official, daily Bank of Canada intervention in the CAD/USD exchange rate market over the January 1995 to September 1998 period. Using an event study methodology and different criteria for effectiveness, movements in the CAD/USD exchange rate over the 1 through 10 days surrounding intervention events are investigated. It is shown that Bank of Canada intervention was systematically associated with both a change in the direction and a smoothing of the CAD/USD exchange rate. Bank of Canada intervention did not, however, succeed in reducing the volatility of the CAD/USD exchange rate. Additionally, the paper introduces the issue of currency co-movements to the intervention literature. It is shown that the effects of intervention are weakened when adjusting for general currency co-movements against the USD, suggesting that currency co-movements should be taken into account when addressing the effects of central bank intervention aimed at managing a minor currency vis-à-vis a major currency.
Keywords: E58; F31; G14; G15; 330; foreign exchange intervention; event studies; currency co-movement; Wechselkurspolitik; Wechselkurs; US-Dollar; Schätzung; Kanada